Home blood glucose monitoring in insulin-dependent diabetic children - Hoon, Tan Siok; Wah, Lee Bee; Boon, Wong Hock (The Turkish Journal of Pediatrics, 1983)
All 12 insulin-dependent diabetic children on regular follow-up in the Department of Paediatrics were taught HBGM. Their ages ranged from 4.9 to 17.2 years (mean 11.7 years). Blood glucose levels were determined before each meal and before bedtime using Ames Dextrostix and Dextrometers. They had previously been monitored by urine sugar testing and periodic blood glucose estimations and considered to be under satisfactory control with their initial insulin regimes.HBGM showed wide fluctuations in 24-hour blood glucose levels in 11 patients on their initial insulin regimes. Using HBGM, their insulin regimes were adjusted to achieve normoglycemia. The mean blood glucose before and after HBGM dropped from 250 mg/dl to 150 mg/dl (p < 0.001). Hospital admissions and outpatient visits were reduced following HBGM. Eleven patients found HBGM useful, felt symptomatically improved and complained only of sore fingers. There was a significant drop in HbA₁ values after HBGM.Our study shows that HBGM is feasible and useful even in young children, who would benefit most from good diabetic control.
Keywords: diabetes mellitus; home blood glucose monitoring